1984
DOI: 10.1038/309327a0
|View full text |Cite
|
Sign up to set email alerts
|

Kinked DNA in crystalline complex with EcoRI endonuclease

Abstract: The 3 A electron density map of a co-crystalline recognition complex between EcoRI endonuclease and the oligonucleotide TCGCGAATTCGCG reveals that a tight, complementary interface between the enzyme and the major groove of the DNA is the major determinant of sequence specificity. The DNA contains a torsional kink and other departures from the B conformation which unwind the DNA and thereby widen the major groove in the recognition site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0
1

Year Published

1985
1985
1992
1992

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(107 citation statements)
references
References 47 publications
3
103
0
1
Order By: Relevance
“…(0) respectively (14,15). The role of unwinding is uncertain, although it may be a mechanism for recognition of specific sequences (15). For RNA polymerase, the unwinding angle measured has varied between 2400 (7 bases) to 5800 (17 bases) and has been suggested to be a part of the mechanism for the formation of the 'open complex' required for initiation of RNA synthesis (16,17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(0) respectively (14,15). The role of unwinding is uncertain, although it may be a mechanism for recognition of specific sequences (15). For RNA polymerase, the unwinding angle measured has varied between 2400 (7 bases) to 5800 (17 bases) and has been suggested to be a part of the mechanism for the formation of the 'open complex' required for initiation of RNA synthesis (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…The gels were stained 6 hrs in 2 Mg/ml ethidium bromide (with gentle shaking), destained for 0. (0) respectively (14,15). The role of unwinding is uncertain, although it may be a mechanism for recognition of specific sequences (15).…”
Section: Methodsmentioning
confidence: 99%
“…In their X-ray crystallographic study of the influence of base sequence on helix structure in the dodecamer [d(CGCGAATTCGCG)],, Dickerson and Drew [6] reported several structural deviations or purine-pyrimidine sequences relative to purine-purine or pyrimidine-pyrimidine sequences. The six internal residues in the Dickerson sequence and in the [7] have performed Xray analysis of the EcoRI endonuclease co-crystallized with the tridecamer [d(TCGCGAATTCGCG)I2 (again, the central six-base sequence is the EcoRI site) and found that at the GAA-TTC junction, there is a kink. Although comparison of the oligonucleotide structure in the co-crystal with that of the dodecamer in the 'pure' crystal lead Frederick et al to suggest that their structure requires the enzyme for stability, they further suggest that this kinked conformation may exist transiently for the oligonucleotide alone in solution [7].…”
Section: Theoretical (Upper Triangle) Andexperimental (Lower Triangmentioning
confidence: 99%
“…The six internal residues in the Dickerson sequence and in the [7] have performed Xray analysis of the EcoRI endonuclease co-crystallized with the tridecamer [d(TCGCGAATTCGCG)I2 (again, the central six-base sequence is the EcoRI site) and found that at the GAA-TTC junction, there is a kink. Although comparison of the oligonucleotide structure in the co-crystal with that of the dodecamer in the 'pure' crystal lead Frederick et al to suggest that their structure requires the enzyme for stability, they further suggest that this kinked conformation may exist transiently for the oligonucleotide alone in solution [7]. In any case, there is evidence for some type of conformational change in this hexamer sequence at the site of transition from purine to pyrimidine.…”
Section: Theoretical (Upper Triangle) Andexperimental (Lower Triangmentioning
confidence: 99%
“…Since the preference of cleavage is inversely correlated to the thermal stability of the oligodeoxynucleotide substrates, it might also be that in the course of the recognition process, a structural transition of the substrate is induced, as was reported for the EcoRI . DNA complex [30]. The feasability of this transition might depend on the stability of the duplex structure in this region.…”
Section: Discussionmentioning
confidence: 99%